Cervical-Flexion Rotation Test and Cervical Mobility in Normal and Cervicogenic Headache Patients - Asma Ilyas, Wajeeha Zia, Irfan Bashir, Sheher Bano, Muhammad Salman Bashir, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The root of the word "cervicogenic headache" was in 1983. "Cervicogenic headache is a secondary headache caused by neck fractures, infections and hypertension. Cervicogenic headache pain occurs in the neck and back of the head and radiates to the front of the head. Aims: To compare the results of the cervical flexion-rotation test (FRT) and cervical mobility between subjects with cervicogenic headache (CGH) and asymptomatic headache (CGH). Test of flexion-rotation conducted to determine cervicogenic headache. Methods: This research was comparative and used to assess the distinctions between asymptomatic subjects and those with subjective cervicogenic headache characteristics. In this study 10 participants paired with 10 asymptomatic subjects with side dominant cervicogenic headache. A total of 20 participants were screened and distributed into treatment / case and control groups according to selection criteria. The severity of headaches was measured using a questionnaire. The goniometer was used to measure the cervical range of motion in both groups at pre- and post-treatment stages. Data was analyzed by SPSS. Results: 50% participants are in age-group of 20-29, 20% participants are in age-group of 30-39, 15% participants are in age-group of 40-49 and 15% participants are in age-group of 50 or above. Conclusion: It is concluded that in asymptomatic subjects, ROM was normal with no pain during cervical flexion rotation test.